2022
DOI: 10.1038/s41598-022-16279-z
|View full text |Cite
|
Sign up to set email alerts
|

Treatment resistance of rheumatoid arthritis relates to infection of periodontal pathogenic bacteria: a case–control cross-sectional study

Abstract: Recent studies have shown that periodontitis is associated with rheumatoid arthritis (RA) and periodontal bacteria, such as Aggregatibacter actinomycetemcomitans (Aa) and Porphyromonas gingivalis (Pg) are involved in the pathogenesis of RA via citrullinated proteins. Smoking has also been shown to be involved in the pathogenesis of RA; however, the extent of this involvement is still poorly understood. In addition, RA and polymyalgia rheumatica (PMR) are sometimes difficult to differentiate; however, the relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 58 publications
(54 reference statements)
1
3
0
1
Order By: Relevance
“…The results indicated a significantly higher ESR and a trend toward a higher DAS28-ESR in 16 RA patients positive for anti- P. gingivalis IgG than in 22 RA patients without anti- P. gingivalis IgG [78] . Similar results were obtained in recent studies [141] , [142] , and both concluded that baseline serum anti- P. gingivalis IgG, but not anti- A. actinomycetemcomitans IgG, was predictive of the response to treatment with bDMARDs and csDMARDs. However, these are serum IgG responses to sonicated preparations of P. gingivalis , and their target antigens are unclear.…”
Section: Publications 2013–2022supporting
confidence: 88%
See 1 more Smart Citation
“…The results indicated a significantly higher ESR and a trend toward a higher DAS28-ESR in 16 RA patients positive for anti- P. gingivalis IgG than in 22 RA patients without anti- P. gingivalis IgG [78] . Similar results were obtained in recent studies [141] , [142] , and both concluded that baseline serum anti- P. gingivalis IgG, but not anti- A. actinomycetemcomitans IgG, was predictive of the response to treatment with bDMARDs and csDMARDs. However, these are serum IgG responses to sonicated preparations of P. gingivalis , and their target antigens are unclear.…”
Section: Publications 2013–2022supporting
confidence: 88%
“…Since 2013, eight original intervention studies have been conducted to assess the effect of periodontitis and periodontopathic bacterial infection on the response to pharmacological treatment with DMARDs in RA patients [78] , [137] , [138] , [139] , [140] , [141] , [142] , [143] . A summary of the study method and outcome in each study is presented in Table 2 .…”
Section: Publications 2013–2022mentioning
confidence: 99%
“…It has been demonstrated that all periodontal indexes are worse in RA patients, with an adjusted odds ratio of 2.66 [87]. There is also a linear correlation between clinical and laboratoristic parameters of RA and periodontitis, such as the high Disease Activity Score Calculator for Rheumatoid Arthritis (DAS28), RF, ACPAs, CRP, ESR, and disease duration [88][89][90][91].…”
Section: Discussionmentioning
confidence: 99%
“…Авторы предполагают, что антитела IgA против RgpB в слюне могут быть связаны с активностью заболевания РА. В японском перекрестном исследовании «случай -контроль» [95] отмечено, что пародонтальные патогенные бактерии, особенно P. gingivalis, связаны с повышенным уровнем ACPA. Пациенты с РА, которые имели высокие титры антител, имели плохой ответ на терапию.…”
Section: эпидемиологические и клинические исследованияunclassified